Moult migration, site fidelity and survival of Canada Geese Branta canadensis caught at Lake Windermere, Cumbria - Brides, Kane; Wood, Kevin A.; Leighton, Kevin R.; Barbour, Jude; Petrek, Scott W.; Cooper, Jonathan; Vickers, Stephen H.; Christmas, Stephen E.; Middleton, Jon; Grogan, Adam (Wildfowl, 2023)
Analyses of 2,108 re-encounters made during 2013–2021 of 1,042 Canada Geese Branta canadensis marked at Windermere, Cumbria, in summers 2013–2021 are used to describe their post-moult migration site linkages. Birds moulting at Windermere were subsequently sighted in 34 counties, although post-moult migration was mainly to the counties of Lancashire, Cheshire and Cumbria itself. The proportions of re-encounters in each direction away from Windermere differed statistically from the pattern expected for random dispersal, for seven out of eight directions. Resightings at Windermere showed that the number of marked individuals returning to moult decreased during the study, although numbers moulting on Windermere remained consistent throughout. We also provide new and updated information on the survival and mean dispersal distance for non-breeding Canada Geese. The mean dispersal distance away from Windermere for all marked individuals was 76 km (95% CI = 14.2). Annual mean survival rates ranged between 0.510 and 0.875 over the study period, with a geometric mean of 0.654 ± 0.199 (95% CI = 0.556–0.751). The results significantly improve our knowledge of the demography of the non-native British Canada Goose population.